PENGARUH PENDEKATAN MATEMATIKA REALISTIK DAN KETERAMPILAN MEMBACA TERHADAP KEMAMPUAN PEMECAHAN MASALAH SOAL CERITA PADA SISWA SEKOLAH DASAR - Budiharti dan Deri Anggraini (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
This study aim to: 1) describe the effect of realistic mathematic approach to problem solvingabilities in word problems in elementery school students, 2) describe the influence of reading skills inproblem solving skills in word problems in elementary school students, and 3) describes the influenceof the interaction realistic mathematics approach and reading skills of problem solving abilities. Thisstudy was a quasy experimental study with a Postest only non-ekuivalen multiple-group design, usingexperimental and control groups. The pupulation in this study were elemenary school students in theDisctrict Kasihan Bantul. Sampling through stratified cluster random sampling based on ranking inthe acquisition of the average value UASBN 2010. The data analysis technique used in this study is astatisctical technique to test a 2 x 3 analysis of variance. The result of this study are: 1) realisticmathematical approach effect on problem solving in word problems in elementary school students, 2)reading skill effect on the problem solving in word problem in elementary school, 3)Â  realisticmathematical approach and reading skill interaction doesnt effect on problem solving ability